The impact of direct nucleation control on crystal size distribution in pharmaceutical crystallization processes - Abu Bakar, Mohd Rushdi; Nagy, Zoltan K.; Saleemi, Ali N.; Rielly, Chris D. (American Chemical Society, 2009)
The control of crystal size distribution (CSD) in pharmaceutical crystallization is of primary importance, as downstream processes such as filtration or drying are greatly affected by the properties of the CSD. It is recognized that the variability in the final CSD is mainly caused by the significant uncertainties in the nucleation rates, and therefore, a good control of nucleation events is necessary to achieve the desired CSD. In this paper, a new direct nucleation control (DNC) approach is introduced that directly controls the apparent onset of nucleation defined as the formation of new particles with detectable size using in situ instruments. The approach uses information on nucleation and dissolution, provided by focused beam reflectance measurement (FBRM), in a feedback control strategy that adapts the process variables, so that the desired quality of product is achieved, for example large crystals with a narrow CSD. In addition, DNC provides in situ fines removal through the operating protocol, rather than having additional equipment and external recycle loops. DNC does not require concentration measurement and has the advantage of being a model-free approach, requiring no information on nucleation or growth kinetics in order to design an operating curve. The DNC approach automatically and adaptively detects the boundary of the operating zone; hence it is more robust to the presence of impurities or residual solvent than the supersaturation control approach. The approach has been applied for the crystallization of glycine and experimental results demonstrate the benefits of DNC of producing larger crystals with narrower CSD compared to classical operations.